2003
DOI: 10.1016/s0165-2370(03)00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical–structural characterization of solvent and thermal extractable material from perhydrous vitrinites

Abstract: In this work, the characterization of the non-covalently bonded compounds present in a set of perhydrous coals of different age and geographical location (Cretaceous coals: UCV and TCV and Jurassic coals: AJV, PGJV, WJVh and WJVl) was carried out by means of a combination of the analyses of the material soluble in chloroform and the thermal extract. The extract in chloroform was studied through GC/MS and NMR and the thermovaporized fraction was obtained by means of flash pyrolysis at the Curie temperature of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…1b) agrees with several common characteristics previously reported for these samples [1]. In particular, this supports the view that between the two types of non-covalent bonded compounds described for the PGJV [6] coal, those of a more aromatic nature and structurally similar to those assimilated in the coal matrix of the AJV coal are mainly responsible for the perhydrous character of this coal.…”
Section: Solid Residuessupporting
confidence: 90%
See 4 more Smart Citations
“…1b) agrees with several common characteristics previously reported for these samples [1]. In particular, this supports the view that between the two types of non-covalent bonded compounds described for the PGJV [6] coal, those of a more aromatic nature and structurally similar to those assimilated in the coal matrix of the AJV coal are mainly responsible for the perhydrous character of this coal.…”
Section: Solid Residuessupporting
confidence: 90%
“…The sources of hydrogen-rich material were, however, different for each coal. Evidence of incorporation of hydrogen-rich compounds from the primary decomposition of organic material in the sedimentary environment was only clearly established for one of the coals studied, WJVl [6]. It has also been shown that assimilation into the coal matrices did not take place at the same stage of diagenetic evolution for all the samples.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations